High heterogeneity of cross-reactive immunoglobulins in multiple sclerosis presumes combining of B-cell epitopes for diagnostics: a case-control study - Ovchinnikova, Leyla A.; Eliseev, Igor E.; Dzhelad, Samir S.; Simaniv, Taras O.; Klimina, Ksenia M.; Ivanova, Maria; Ilina, Elena N.; Zakharova, Maria N.; Illarioshkin, Sergey N.; Rubtsov, Yury P.; Gabibov, Alexander G.; Lomakin, Yakov A. (Frontiers in Immunology, 2024)
BackgroundMultiple sclerosis (MS) is a neuroinflammatory disease triggered by a combination of genetic traits and external factors. Autoimmune nature of MS is proven by the identification of pathogenic T cells, but the role of autoantibody-producing B cells is less clear. A comprehensive understanding of the development of neuroinflammation and the identification of targeted autoantigens are crucial for timely diagnosis and appropriate treatment.MethodsAn expression library of 44-mer overlapping peptides from a panel of putative autoantigenic human proteins was employed for modified Phage ImmunoPrecipitation Sequencing (PhIP-Seq) to identify B cell peptide epitopes from MS patients. Individual peptides extracted by PhIP-Seq were tested by ELISA to characterize their affinity towards IgG from both MS patients and healthy donors (HD). Three candidate auto-peptides were used for isolating autoreactive antigen-specific IgGs from the serum of MS patients.ResultsAutoantibody screening revealed high heterogeneity of IgG response in MS. The autoantigenic genesis of the PhIP-Seq-identified peptides was further strengthened by clinical ELISA testing of 11 HD and 16 MS donors. Validation experiments on independent cohorts of 22 HD and 28 MS patients confirmed statistically significant elevated titers of IgG specific to spectrin alpha chain (SPTAN1) in the serum of MS patients compared to HD. The levels of anti-SPTAN1 IgG correlated in serum and cerebrospinal fluid (CSF). Isolated autoreactive antigen-specific IgG exhibited increased cross-reactivity to a panel of PhIP-Seq-identified antigenic peptides. Serum IgG from MS patients were reactive to latent membrane protein (LMP1) of Epstein-Barr virus, a potential trigger of MS. Discovered antigenic peptides from SPTAN1, protein-tyrosine kinase 6 (PTK6), periaxin (PRX), and LMP1 were tested as potential biomarker panel for MS diagnostics. We concluded that the combination of particular peptides from SPTAN1, PTK6, PRX and LMP1 could be implemented as a four-peptide biomarker panel for MS diagnosis (area under the curve (AUC) of 0.818 for discriminating between HD and MS).ConclusionsThis study supports the concept that the specificity of autoreactive IgG in MS is highly heterogeneous. Despite that we suggest that the combination of several B-cell epitopes could be employed as reliable and simple test for MS diagnostics.